A Photoexcitation‐Induced Twisted Intramolecular Charge Shuttle. (12th April 2019) - Chi, Weijie; Qiao, Qinglong; Lee, Richmond; Liu, Wenjuan; Teo, Yock Siong; Gu, Danning; Lang, Matthew John; Chang, Young‐Tae; Xu, Zhaochao; Liu, Xiaogang
Abstract: Charge transfer and separation are important processes governing numerous chemical reactions. Fundamental understanding of these processes and the underlying mechanisms is critical for photochemistry. Herein, we report the discovery of a new charge‐transfer and separation process, namely the twisted intramolecular charge shuttle (TICS). In TICS systems, the donor and acceptor moieties dynamically switch roles in the excited state because of an approximately 90° intramolecular rotation. TICS systems thus exhibit charge shuttling. TICSs exist in several chemical families of fluorophores (such as coumarin, BODIPY, and oxygen/carbon/silicon–rhodamine), and could be utilized to construct functional fluorescent probes (i.e., viscosity‐ or biomolecule‐sensing probes). The discovery of the TICS process expands the current perspectives of charge‐transfer processes and will inspire future applications.